Mexico : Selected Issues. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2018)
This Selected Issues paper on Mexico documents the composition, trends, and labor market implications of informality using data from the National Employment Survey (ENOE). Over half of the employed population has informal contractual relationships in Mexico both at formal and informal firms. Informality is found to be associated with lower levels of pay-even when accounting for worker composition differences-and lower wage growth over the life cycle. Policy drivers of this market duality, including minimum wage policy, are discussed. The results suggest that informality tends to select workers with lower earnings potential and limits their development. Informality indeed tends to be more prevalent among younger and less educated workers, for which better paid jobs are harder to come by. Moreover, it appears to lead workers toward a path of limited earnings and perhaps skill growth potential. Future labor market reforms should take a holistic approach that addresses both distributional concerns and formality barriers. One alternative is to reduce dependence on payroll taxes that are biased toward formal salaried workers while transitioning toward a social insurance system that provides good-quality services for all, irrespective of their salaried/nonsalaried status.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet